The Influence of Social Media Marketing Activities on Consumer Purchase Interest in Bottled Drinking Water Brands (AMDK) - Christiarini, Renny; William; Edy Yulianto Putra (Program Sarjana Manajemen Universitas Internasional Batam, 2024)
The objective of this study is to examine the purchase intention of bottled drinking water (AMDK) in Batam. The sample gathered consists of 400 social media user and consumers of AMDK brand in Batam. The main data was collected via an online surveys using Google Forms. The method of sampling utilized is non-probability sampling. This research uses quantitative analysis methods with the Partial Least Squares (PLS) and data processing and testing using SPSS Statistic. The research findings indicate that elements including entertainment, engagement, current fashion, customization, and e-WOM have a significant positive impact on brand awareness and brand image. However, interaction does not show a significant positive impact on brand awareness. Brand awareness and brand image significantly impact on purchase intention.